Assessing Corporate Social Responsibility Disclosures in Lithuania’s Largest Banks - Račaitė, Sabina; Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2024)
The article examines the importance and regulation of corporate social responsibility disclosure. Based on the GRI standards and the recommendations of the Bank of Lithuania, the paper develops a methodology for calculating the corporate social responsibility index and a model for assessing its quality. The paper presents the results of an empirical study conducted to assess the disclosure of corporate social responsibility in the financial statements of the largest Lithuanian banks in the period 2018-2022. The results show that Lithuanian banks tend to disclose more than 91% of the recommended socially responsible information, while the quality of the reports, according to the selected criteria, reaches 64-82%. Nevertheless, it was noted that some banks do not produce CSR reports and publish group reports in languages other than Lithuanian. Some reports show signs of poor quality: the objectives are not specific and measurable and the textual information is repetitive throughout the study period.